Evaluation of the psychometric properties of the SF-36 health survey for use among Turkish and Moroccan ethnic minority populations in the Netherlands - Hoopman, Rianne (Springer Netherlands, 2009)
PURPOSE: To evaluate the psychometrics of the SF-36 Health Survey among Turkish and Moroccan ethnic minority populations in the Netherlands and to compare the results to those based on the indigenous Dutch population. METHODS: Data were derived from the Second Dutch National Survey of General Practice. In total, SF-36 data were available for 409 Turkish, 377 Moroccan, and 9,628 Dutch respondents. Language subgroup analyses were performed for the Turkish (n = 162) and Moroccan-Arabic (n = 52) versions of the SF-36. Psychometric properties were evaluated by descriptive statistics, factor analysis, internal consistency estimates, known-group comparisons, and differential item function (DIF) analysis. RESULTS: Low levels of missing SF-36 data were observed across all groups. Confirmatory factor analysis supported the hypothesized SF-36 scale structure for the Dutch and Turkish group, but high correlations between the MH and VT factors were observed in the Moroccan group. All Cronbach’s alpha coefficients were above 0.70, except for the Vitality scale in the Moroccan group and the Vitality and Social Functioning scales in the Moroccan-Arabic language subgroup. Known-groups validity was found across samples using age, sex, education, and comorbidity as grouping variables, but not marital status. Some evidence for DIF was found in both ethnic group samples. CONCLUSIONS: The results generally support the use of the SF-36 for general population research among Turkish and Moroccan ethnic minorities in the Netherlands. Additional studies are needed to confirm the psychometrics of the questionnaire when used among these populations in other Western European countries.